THE EFFECT OF COMPANY CHARACTERISTICS, AUDIT QUALITY, AND TAX PLANNING ON BOOK TAX DIFFERENCES (BTD) AND IMPACT ON PERSISTENCY OF PROFIT - Fadhril Rahmi Yulianto; Emrinaldi Nur DP; Andreas Andreas (PEKBIS, 2020)
This study aims to examine and analyze the effect of company characteristics, auditquality, and tax planning on book tax differences (BTD) and their impact on earningspersistence. The population in this study are companies listed on the IndonesiaStock Exchange (IDX) in the 2014-2016 period. While the samples chosen wereforeign investment companies (PMA). The sampling technique used purposivesampling method, the researcher determined as many as 28 companies with a totalobservation of 84 samples. Data analysis was performed with multiple linearregression models and independent sample t test with the help of SPSS version21.0 software. The results of the study show that profitability and tax planning affectbook tax differences (BTD). While leverage, liquidity, and audit quality do not affectbook tax differences (BTD). Furthermore, for the second model, the results obtainedthat permanent differences affect the persistence of earnings. However, fortemporary differences does not affect the persistence of earnings. From the resultsof the independent sample t test showed that in the first model the percentage of theinfluence of the independent variable on the dependent variable was 83.4%.Whereas in the second model, the percentage effect of variables on the dependentvariable is 12.1%.